Reluctant empiricists: community mental health nurses and the art of evidence-based praxis. - Crawford P; Brown B; Anthony P; Hicks C (Health & Social Care in the Community, 2002)
The National Service Framework for Mental Health (1999) emphasizes the need for a culture of evidence-based practice (EBP) in mental health care. However, there is relatively little research addressing EBP from the perspective of community mental health nurses and we are still unsure of why the uptake of this style of working has been slow. This paper suggests that rather than thinking in terms of 'barriers' to the uptake of EBP, the issue may best be conceptualized as a form of praxis on the part of nurses, as they seek to manage the diversity of ideologies and practices in their working lives. From an interview and focus group study, we identify how practitioners' narrow definition of EBP itself, their formulation of how EBP was at odds with the nurse's professional activity and the organizational constraints within which they work were perceived to inhibit access to information and offer little time and managerial support for information seeking. Those who attempt to further the involvement of community mental health staff in EBP will have to reconceptualize the reasons why staff have yet to incorporate it fully, and acknowledge that this does not occur because staff are simply 'ignorant Luddites', but that this resistance enables them to retain a sense of control over their working lives and retain a focus on work with clients. Future EBP initiatives will have to address these ideological and organizational factors in order for uptake to be accelerated. This may involve changing organizational cultures and work roles and even encouraging activism on the part of the practitioners so as to enable them to learn from each other and educate and change their work environments.